Hypogonadism and Sexual Dysfunction in Testicular Tumor Survivors: A Systematic Review - La Vignera, Sandro; Cannarella, Rossella; Duca, Ylenia; Barbagallo, Federica; Burgio, Giovanni; Compagnone, Michele; Di Cataldo, Andrea; Calogero, Aldo E.; Condorelli, Rosita A. (Frontiers in Endocrinology, 2019)
Testicular tumor is the most common malignancy in men of reproductive age. According to the tumor histology and staging, current treatment options include orchiectomy alone or associated with adjuvant chemo- and/or radiotherapy. Although these treatments have considerably raised the percentage of survivors compared to the past, they have been identified as risk factors for testosterone deficiency and sexual dysfunction in this subgroup of men. Male hypogonadism, in turn, predisposes to the development of metabolic and cardiovascular impairment that negatively affects general health. Accordingly, longitudinal studies report a long-term risk for cardiovascular diseases after radiotherapy and/or cisplatin-based chemotherapy in testicular tumor survivors. The aim of this review is to summarize the current evidence on hypogonadism and sexual dysfunction in long-term cancer survivors, including the epidemiology of cardiovascular and metabolic disorders,to increase the awareness that serum testosterone levels, sexual function and general health should be evaluated during the endocrinological management of these patients.